Attitude, Belief, and Perception Toward Mental Illness Among Indian Youth - Akshat Chowdhury; Kavita Gupta; Ashok Kumar Patel (MAMC Journal of Medical Sciences, 2019)
Background: According to World Health Organization (1999), mental health is defined as “subjective well-being, perceived self-efficacy, autonomy, competence, intergenerational dependence, and self-actualization that deals with the individual’s awareness, attitude, and belief about the mental disorders.” Hence, the present study was conducted among Indian college students to assess belief, attitude, and perception about causes and treatment of mental disorder (illness) with respect to depression and schizophrenia. Material and Methods: The present descriptive study was undertaken at Amity university, Rajasthan, with a sample of 150 college undergraduate and postgraduate students in the age group of 18 to 27 years by using cases “Vignettes of Depression and Schizophrenia” and “Short Version of Orientation Toward Mental Illness Scale (OMI).” Results: The present study indicated that depression was easily recognizable as compared to schizophrenia among college students. Stressful factors were considered as the primary cause for both depression and schizophrenia. Majority of the participants were convinced of the favorable outcome of both depression and schizophrenia. Conclusion: It was concluded that majority of the participants had negative attitude toward folk therapy, psychosocial manipulation, and physical method of treatment with the perception of family as a main source for seeking help regarding mental illness. Moreover, majority of participants had a belief that mental disorder is a cause for depression and stress is the main cause for schizophrenia among the mental illness. Therefore, the prognosis of both depression and schizophrenia was considered good.